Atmospheric concentration and carcinogenic risk of polycyclic aromatic hydrocarbons including benzo[c]fluorene, cyclopenta[c, d]pyrene, and benzo[j]fluoranthene in Japan. (August 2015) - Yagishita, Mayuko; Kageyama, Shiho; Ohshima, Shigeru; Matsumoto, Michi; Aoki, Yasunobu; Goto, Sumio; Nakajima, Daisuke
Abstract: The atmospheric concentrations of both gas-phase and particulate-phase polycyclic aromatic hydrocarbons (PAHs) including 16 US Environmental Protection Agency priority PAHs (16 PAHs) were measured in eleven cities across Japan. Using the measured average concentrations and toxic equivalency factors (TEF) of the 16 PAHs, the benzo[ a ]pyrene (BaP)-toxic equivalent for eight major PAHs was obtained: the ratio of BaP to the eight major PAH toxicities ranged from 0.23 to 0.47. Among the target PAHs, from the viewpoint of carcinogenicity, we focused on benzo[ c ]fluorene (BcFE), which was detected in both the gas and particulate phase in contrast to BaP. The relative potency factor (RPF) of BcFE was evaluated as 6.46 based on its cancer slope factor relative to that of BaP determined in the benchmark dose calculations for mice. The relative carcinogenic risk of BcFE to BaP was obtained by multiplying the averaged concentrations of BaP and BcFE by the RPF value: the risk of BcFE was 6.8 and 5.1 times higher than that of BaP in summer and winter, respectively. These results show that the collection of atmospheric samples including the gas phase is important when assessing the carcinogenic risk of atmospheric PAHs. Highlights: Overall atmospheric concentration levels of PAHs across Japan were measured. Atmospheric concentrations of BcFE, CPcdP, and BjF were similar to that of BaP. Benchmark dose method was applied to evaluate carcinogenic risk. Carcinogenic risk of BcFE for mice was 5–7 times higher than that of BaP.